Accuracy and convergence of element-by-element iterative solvers for incompressible fluid flows using penalty finite element model - Reddy, M. P author; Reifschneider, L. G author; Reddy, J.N author; Akays, H. U author (United States : John Wiley and Sons, 1993)
PSZJBL